2014
DOI: 10.1038/ijo.2014.124
|View full text |Cite
|
Sign up to set email alerts
|

Gamma-tocotrienol attenuates high-fat diet-induced obesity and insulin resistance by inhibiting adipose inflammation and M1 macrophage recruitment

Abstract: Our results demonstrated that γT3 ameliorates HF diet-mediated obesity and insulin resistance by inhibiting systemic and adipose inflammation, as well as ATM recruitment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
95
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(101 citation statements)
references
References 47 publications
6
95
0
Order By: Relevance
“…Assuming that macrophages in adipose tissue are the source of the mediators of chronic low-grade inflammation [57], reduction in adipose tissue would decrease the proinflammatory microenvironment in this tissue. As δ-tocotrienol reduced the infiltration of inflammatory cells in the heart and liver, this action in combination with reduction in fat depots may improve the metabolic disorders in treated obese rats [58]. Further, liver function was not compromised in δ-tocotrienol-treated rats despite continuation of the high intake of saturated fats and simple sugars.…”
Section: Plasma and Tissue Concentrations Of α-Tocopherol α- γ-And mentioning
confidence: 96%
“…Assuming that macrophages in adipose tissue are the source of the mediators of chronic low-grade inflammation [57], reduction in adipose tissue would decrease the proinflammatory microenvironment in this tissue. As δ-tocotrienol reduced the infiltration of inflammatory cells in the heart and liver, this action in combination with reduction in fat depots may improve the metabolic disorders in treated obese rats [58]. Further, liver function was not compromised in δ-tocotrienol-treated rats despite continuation of the high intake of saturated fats and simple sugars.…”
Section: Plasma and Tissue Concentrations Of α-Tocopherol α- γ-And mentioning
confidence: 96%
“…In the obese animal model, a study by Zhao et al (2015) indicated that the marked increase in fasting blood glucose (FBG), insulin, fat content (mesenteric and epididymal), body weight, liver weight, and pro-inflammatory cytokines in high-fat diet-induced obese animals were efficiently counteracted by γT3 supplementation. An in vivo experiment by Alcala et al (2015) demonstrated that obese mice fed on high-fat diet and supplemented twice a week with αTF (150 mg/kg) improved insulin sensitivity and hypertriglyceridemia, implicated through the reduction of oxidative stress and inflammatory response.…”
Section: Effects Of Vitamin E On Mets Features In Animal Modelsmentioning
confidence: 99%
“…Meanwhile, the three most abundant sources of T3 are rice bran (50%), palm (75%), and annatto (99.9%) (Aggarwal et al, 2010). Recently, interest in the health benefits of vitamin E increased rapidly as emerging evidence on the anti-obesity (Zhao et al, 2015), anti-hypercholesterolemic (Zaiden et al, 2010), anti-diabetic (Budin et al, 2009; Matough et al, 2014), and anti-hypertensive (Newaz et al, 2003) effects of vitamin E has been reported. Both TF and T3 have been demonstrated to improve metabolic abnormalities in animal and human studies with varying levels of biological activity.…”
Section: Introductionmentioning
confidence: 99%
“…Total cell and tissue extract preparation and Western blot procedures were conducted as we described previously ( 5 ). The antibodies recognizing phospho(p)-p38(Thr180/182), TNF-␣ interacting protein 3 (A20/TNFAIP3), ATG5, p-IKK ␣ / ␤ (Ser176/180), K63-linkage polyubiquitin, K48-linkage polyubiquitin, p-p44/42-ERK1/2 (Thr202/204), total (t)-ERK, p-AMPK ␣ (Thr 172), t-AMPK, ␤ -actin, LC3, p62, Beclin-1, I B ␣ , and p-I B ␣ (Ser32/36 ) were purchased from Cell Signaling Technology.…”
Section: Immunoblotting Immunoprecipitation and Elisamentioning
confidence: 99%